‘Perticular Or Particular? In Search of When English Calvinistic Baptists Became Particular Baptists’ - Brackney, William H. (Baptist quarterly, 2022)
The terminology ‘Particular Baptist’ has been employed by early and contemporary writers to denominate English Calvinistic Baptists since Thomas Crosby's published history in 1738–40. However, upon closer scrutiny of original manuscripts, the terminology ‘Particular Baptists’ did not come into usage until the 1680s. Instead of Particular Baptists being defined by a limited view of Christ's atonement (i.e. for a particular group), the earliest Calvinistic Baptists created a theological identity built upon their doctrine of the church, as articulated in the London Confession of 1644. This essay surveys key writers and documents to demonstrate a two-stage theological development that focussed initially upon particular congregations, and later upon classic Calvinistic principles such as election, predestination, and perseverance. Gradually the ‘Particular Baptist’ nomenclature came into use to denote the English Calvinistic Baptists in contrast to general atonement or Arminian Baptists. In the period 1640–1680, the preferred terminology is simply Calvinistic Baptists.